How can we define normal? And how would you describe mental illness to someone who knew nothing about the topic? (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Essay Prompt: An alien ship drops out of the sky from another planet. Unfortunately (or fortunately, depending on your viewpoint), they have been watching Youtube videos of the Kardashians and other reality shows while traveling to our planet, and they are very confused about what is a “normal” human being. So far in class we have interviewed three different patients with three different mental illnesses. If we follow through with this logic, then persons without a “diagnosis” are apparently “normal.” How would you explain mental illness to an alien who has no biases or knowledge of what it is like to have a mental illness? How would you decide what is normal and what is abnormal? Who should decide what is normal? In the passage above, leading psychiatrists were the ones deciding normal versus abnormal for the world. Please write an essay considering one or more of the questions detailed here in this prompt (or ask and answer your own question!), drawing on the passage above, class interviews, optional reading, and/or your own experiences.
Keywords: NSCI1000